Cultivating Founders: How Policy and Education Intersect in Indonesian and Malaysian Universities - Abdullah Sumrahadi; Musa Maliki; Andika Priyandana Sunoko; Harryanto Aryodiguno (Madani Connection, 2025)
This study presents an up-to-date comparative analysis of entrepreneurship education in Indonesia and Malaysia, focusing on academic papers published from 2021 to 2023, with a research timeframe spanning from 2009 to 2022. Employing a qualitative meta-analysis research approach, the study utilizes thematic analysis to identify recurring themes and patterns in the literature. The thematic analysis of academic papers on entrepreneurship education in Indonesia’s higher education uncovers four key themes: entrepreneurial mindset and competence, challenges and barriers in entrepreneurship education, blended learning framework in Entrepreneurship Education Programs (EEPs), and entrepreneurial interests and personal alignment. Conversely, the thematic analysis of academic papers concerning entrepreneurship education in Malaysia's higher education context reveals four distinct themes: the role of entrepreneurship education, factors influencing entrepreneurial intentions and their interplay within the entrepreneurial ecosystem, the mediating role of entrepreneurship education and its impact on the entrepreneurial ecosystem, and policy and institutional implications. This comparative study provides valuable insights into Indonesia and Malaysia's unique approaches and challenges in fostering entrepreneurship education within their respective higher education systems.